Promising indicators for effectively targeting the poor in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Social protection in Myanmar is currently very limited, and scarce development partner resources should be as accurately targeted to needy populations as possible, based on observable and verifiable characteristics. This note summarizes some promising poverty targeting indicators from the Myanmar Household Welfare Survey (MHWS), conducted by phone among 12,000 households in 310 townships in July/August 2022.